Specific Combination of Salvianolic Acids As Core Active Ingredients of Danhong Injection for Treatment of Arterial Thrombosis and Its Derived Dry Gangrene - Zhao, Tiechan; Chang, Lianying; Zhang, Boyong; Lu, Ming; Wang, Xiaoyi; Orgah, John O.; Wang, Yuefei; Tian, Xiaoxuan; Yang, Jing; Fan, Guanwei; Zhang, Boli; Zhu, Yan (Frontiers in Pharmacology, 2017)
Although single-targeting anti-platelet agents are used extensively in clinics, their limitations in resistance and bleeding have started a trend of combination therapy. Danhong injection (DHI) is a widely prescribed injection medicine for cardiovascular and cerebrovascular diseases in China. However, its precise clinical efficacy and functional components remain unexplored. In this study, we investigated the anti-thrombotic role and its chemical basis of DHI. In a photochemically-induced thrombosis model, DHI effectively dissolved thrombus and ameliorated its derived dry gangrene. DHI inhibited multiple GPCR agonists-induced platelet adhesion, aggregation and downstream Ca2+ and cAMP signaling pathways. A functional screen of DHI library identified its major active components as a cluster of seven salvianolic acids. A combination of salvianolic acid A and C synergistically inhibited platelet aggregation in vitro while salvianolic acid B antagonized this effect. Our study revealed an anti-thrombotic activity of DHI. The multi-targeting mechanism of DHI proves the effectiveness of a natural anti-thrombotic combination therapy. The identification of salvianolic acids as a core anti-thrombotic activity of DHI and the discovery that their different combinations could either synergistically or antagonistically provide a better guidance for safer clinical application and paves the way for further development of DHI.